Ozone depletion. - Favale, M.G. (European Journal of Pediatric Dermatology, 2002)
The term “hole in the ozone layer” is often heard about along with the collateral effects brought about by ultraviolet radiation (UVR). In this report we will try to take a better look at the topic, giving the reader some objective data in regards to the real seriousness of this phenomenon. In the 70’s a research team, the British Antarctic Survey, while monitoring the atmosphere in the Antarctic region, noticed that the quantity of ozone in the Antarctic area had diminished significantly (24). This fact was so surprising that the instruments used to measure ozone was thought to be out of order. Starting from 1985 regular and periodical measurements were carried out in order to reveal the quantity of ozone in the atmosphere. These studies confirmed the results of the previous checks. (...).